Karya Tari Galuik Dantiang Piriang di Era Digital: Kajian Eksistensi - Elfira Rosa Nasution; Yesriva Nursyam; Eva Riyanti; Auliana Mukhti Maghfirah (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study analyzes how the current digital era significantly influences the way the Galuik Dantiang Piriang dance is recognized, valued, and sustained; it aims to understand how this dance continues to thrive in the digital age. A qualitative research method was employed. Drawing on Jean-Paul Sartre’s theory that "existence precedes essence" meaning something acquires meaning through its actual existence and continued presence via actions and lived processes the study reveals that the dance is flourishing both on digital platforms and within the community, as technological advancements facilitate its continued development and preservation.